Good intentions and ICH-GCP: Trial conduct training needs to go beyond the ICH-GCP document and include the intention-to-treat principle. (December 2014) - Browne, Lois H; Graham, Peter H
Background: It is assumed investigators and statisticians fully understand the importance of avoiding missing outcomes and the intention-to-treat principle during design and analysis phases of a randomised controlled trial in order to obtain the most valuable and reliable results. However, many personnel undertaking day-to-day trial conduct and data collection commonly rely exclusively for guidance on the widely implemented, indeed regulated, International Conference on Harmonisation–Good Clinical Practice document as the guideline and standard for trial conduct. Purpose: This article describes adverse consequences of omission of intention-to-treat principles from training for trial personnel and explores the need for training in addition to the International Conference on Harmonisation–Good Clinical Practice guideline document. Methods: Data from the Breast Boost Study were used to illustrate a comparison of actual results, where vigilant senior investigators re-enforced intention-to-treat requirements throughout all aspects of trial conduct with results that could easily have occurred if study personnel did not understand the importance of intention-to-treat principles. Experience as a co-ordinating centre for an international trial (Trans-Tasman Radiation Oncology Group 08.06 Breast STARS) acted as an audit of data-management culture regarding intention-to-treat in Australia and New Zealand. Results: Despite the Breast Boost Study exceeding planned accrual, it was demonstrated that the study, which found a statistically significant result, could have reported a negative or inconclusive result under the scenario of trial conduct personnel having lack of understanding of the importance of avoiding losses to follow-up. Trans-Tasman Radiation Oncology 08.06 co-ordination experience verified that data-management culture in Australia and New Zealand does not adequately recognise intention-to-treat principles, and this is reflected in trial conduct. Limitations: Trial data described are limited to two trials and in the Australian and New Zealand setting. Conclusion: To be both scientifically and ethically valid, guidelines for trial conduct should include and stress the importance of the intention-to-treat principle and in particular avoiding missing outcomes. Our discussion highlights the vitally important role played by personnel involved in day-to-day trial conduct. Inclusion of scientific principles in guideline documents and/or training which goes beyond International Conference on Harmonisation–Good Clinical Practice to include intention-to-treat is essential to achieve robust research results. Related aspects of randomised trial consent and ethics are discussed.